Common molecular profile of multiple structurally distinct warfare arsenicals in causing cutaneous chemical vesicant injury - Ritesh Kumar Srivastava; Suhail Muzaffar; Jasim Khan; Mohit Bansal; Anupam Agarwal; Mohammad Athar (Scientific Reports)
Abstract Skin exposure to arsenicals such as lewisite and phenylarsine oxide leads to severe cutaneous damage. Here, we characterized the molecular pathogenesis of skin injury caused by additionally structurally distinct warfare arsenicals including diphenylchlorarsine (DPCA), diphenylcyanoarsine (DPCYA), diethylchloroarsine (DECA). Cutaneous exposure to DPCA/DPCYA showed marked increase in skin erythema and edema at 6 and 24 h followed by scar formation at 72 h, while DECA did not produce such visual injuries in mouse skin. Clinical observations showed significant increase in Draize score and skin bi-fold thickness in a time-dependent manner. DPCA or DPCYA-exposed skin histology revealed highly inflamed hypodermal areas with infiltrated immune cells at 6 and 24 h, however, epidermal cell necrosis was seen at 72 h. Significantly high number of macrophage infiltration observed at 6 h, whereas peak neutrophil infiltration occurred at 72 h. Number of micro-blisters also increased. However, these effects were nonsignificant following topical DECA exposure. RT-PCR confirmed augmented inflammatory responses in the skin challenged with both DPCA/DPCYA, which accompanied increased ROS and unfolded protein response (UPR) signaling. DECA also increased ROS with changes in UPR. Disrupted tight (Yap/ZO-1) and adherens (Yap/α-Catenin) junction proteins underlie time-dependent apoptotic cell death of epidermal keratinocytes. Thus, these studies identify arsenicals-manifested signaling pathways similar to those of lewisite.